Pengembangan Media Pembelajaran Pop Up Book pada Materi Sistem Organ Pernafasan Manusia Kelas V di SDN 001 Sawah Baru (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study was motivated by the low interest and understanding of students regarding the human respiratory system due to conventional teaching methods that lack interactive media. The aim of this research is to develop and assess the validity level of a Pop-Up Book learning medium for the fifth-grade respiratory system material at SDN 001 Sawah Baru. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the Development stage. Data were collected through interviews, observations, and validations by material, language, and media experts. The validation results showed that the Pop-Up Book achieved a very high level of validity, with an average score of 85.38% from material experts, 92.2% from language experts, and 93.33% from media experts. These findings indicate that the Pop-Up Book is a feasible, attractive, and interactive learning tool that effectively enhances students’ understanding of the human respiratory system. In conclusion, the developed Pop-Up Book is highly valid and potentially applicable for science learning in elementary schools.